Seismic hazard analysis of the southeastern Pamir Frontal Thrust: implications for regional seismic risk patterns - Li, Jinxiang; Yao, Yuan; Tang, Lihua; Hu, Weihua; Wen, Heping; Chang, Xiangde (Frontiers in Earth Science, 2026)
Analyzing seismic hazard risk is crucial for comprehensive risk mitigation and seismic emergency planning. A scientific evaluation of seismic hazard risk is also crucial for strengthening pre-disaster preparedness and reducing disaster losses. The Pamir Frontal Thrust (PFT) fault is the most recent deformation zone that is still active in the late Holocene, with a documented history of earthquakes of magnitude 7.0 or higher. The southeastern section of the fault passes through various densely populated townships, and there are multiple vulnerability factors in the region, which make the southeastern section of the PFT fault at high risk of seismic hazards. This study assesses the current seismic risk of the southeastern section of the PFT fault. The potential for earthquakes in the region is evaluated by analyzing characteristics such as historical seismicity and the rate of fault activity. It analyzes the distribution of ground-shaking impacts in near-fault regions by combining stochastic simulations of high-frequency ground shaking with predictive methods for near-fault effects. Building characteristics are surveyed using an integrated space-air-ground approach. Through the integration of these methods, an in-depth assessment of the seismic hazard risk was conducted. The results show that regions exposed to more intense seismic shaking demonstrate correspondingly higher damage indices, and the densely populated townships in the area with intensity of VIII and above should be paid more attention to. Moreover, under identical intensity circumstances, areas with a high proportion of earth - wood - type houses display greater anticipated damage. And a gridded hazard risk assessment was produced. Seismic risk maps for the region are also provided. It provides the basis for effective disaster prevention and preparation.